The Effect of Blood Pressure Variability on Coronary Atherosclerosis Plaques - Liu, Yue; Luo, Xing; Jia, Haibo; Yu, Bo (Frontiers in Cardiovascular Medicine, 2022)
Hypertension is one of the most important risk factors for coronary heart disease (CHD). The regulation of blood pressure plays a significant role in the development and prognosis of CHD. Blood pressure variability (BPV) refers to the degree of fluctuation of blood pressure over a period of time and is an important indicator of blood pressure stability. Blood pressure fluctuations are complex physiological phenomena, being affected by physiological and pharmacological effects and regulated by behavioral, environmental, hydrodynamic, and neural factors. According to the different time periods for measuring BPV, it can be divided into very short-term, short-term, mid-term, and long-term. Multiple cardiovascular disease animal models and clinical experiments have consistently indicated that abnormal BPV is closely related to coronary events and is a risk factor for CHD independently of average blood pressure. Thrombosis secondary to plaque rupture (PR) or plaque erosion can cause varying blood flow impairment, which is the main pathological basis of CHD. Plaque morphology and composition can influence the clinical outcome, treatment, and prognosis of patients with CHD. Research has shown that PR is more easily induced by hypertension. After adjusting for the traditional factors associated with plaque development, in recent years, some new discoveries have been made on the influence of abnormal BPV on the morphology and composition of coronary plaques and related mechanisms, including inflammation and hemodynamics. This article reviews the impact of BPV on coronary plaques and their related mechanisms, with a view to prevent the occurrence and development of CHD by controlling BPV and to provide new prevention and treatment strategies for the clinical treatment of abnormal blood pressure.